2016
DOI: 10.1111/jan.12884
|View full text |Cite|
|
Sign up to set email alerts
|

The enablers and barriers to continue breast milk feeding in women returning to work

Abstract: Passion and to a lesser extent intention, influenced women's choice. Women's characteristics played a greater role in their infant feeding outcomes than their work environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 36 publications
3
37
0
1
Order By: Relevance
“…In the same view, Sulaiman and his peers, have also indicated that intentions to a lesser extent influence breastfeeding practice (33). Other cultural barriers such as the performance of cultural rites for both mother and baby, as well as the influence of family members were equally necessary (1,9,19,33,36,37).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the same view, Sulaiman and his peers, have also indicated that intentions to a lesser extent influence breastfeeding practice (33). Other cultural barriers such as the performance of cultural rites for both mother and baby, as well as the influence of family members were equally necessary (1,9,19,33,36,37).…”
Section: Discussionmentioning
confidence: 95%
“…In the same view, Sulaiman and his peers, have also indicated that intentions to a lesser extent influence breastfeeding practice (33). Other cultural barriers such as the performance of cultural rites for both mother and baby, as well as the influence of family members were equally necessary (1,9,19,33,36,37). Therefore, the statement that, "Once the child is delivered, he is no more your baby", confirms the practice of a collective culture in the Kassena-Nankana Municipality and explains the cultural restrictions against mothers' intention to breastfeed exclusively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a collective cultural orientation, like that of Ghana, where a person is positioned in a complex network of social relationships, the intention of a mother to exclusively breastfeed is inadequate (35). In the same view, Sulaiman and his peers, have also indicated that intentions to a lesser extent influence breastfeeding practice (33). Other cultural barriers such as the performance of cultural rites for both mother and baby, as well as the influence of family members impacted EBF rates (1,9,19,33,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…These issues include patterns of employment and women's return to work, presence or otherwise of social and familial support mechanisms, and cultural understandings and beliefs around lactation (Liamputtong, 2011;Liamputtong & Kitisriworapan, 2011;Sulaiman, Liamputtong, & Amir, 2016). The above works is echoed in Lam's (2015) assertion, framed by a new materialist, post-constructionist perspective, that the work of bodies exists in a space that is created both out of biological materiality and by cultural meaning-making.…”
Section: Maternal Bodies: Breastfeeding Morality and Identity Workmentioning
confidence: 83%